Evaluation of the potential of functional Hibernation in industrial facilities: a case study of Kirkuk Cement Factory - Mohamed Hussein Gharbi; Burhan Hamad Idham (Global Scientific Publishing, 2024)
Career hibernation is a phenomenon that refers to a state of stagnation or stagnation in the employee's career path, where individuals feel that there is no progress or new challenges in something, and share this belief in feelings of boredom, encourage it, and reduce performance and productivity, so this research aims to understand its causes and its effects on employees in the research sample, and the research model and its hypotheses were built based on research literature, and the following studies were referred to for research criteria, and a research data questionnaire was designed, where (207) questionnaires were distributed, and (207) of them were retrieved to join (97%) and to ensure the stability of the data, the Volkswagen Cronbach test was used, and the path method and matching equations structural hypotheses were used, and the research reached a set of results, the most important of which is that the factor (the psychological factor and the social factor) had an impact on employees, while the factor in which the Functional was involved in organizing research (the professional, organizational and personal dimension) does not support the hypothesis, and therefore this factor has no impact on career hibernation in organizing research
Keywords: Functional hibernation; Functional hibernation dimensions; Kirkuk Cement Plant